Trechos orquestrais para piccolo: o repertório sinfônico de Villa-Lobos - Júlia Donley Mesquita Gonzales (2015)
The project proposed here aims to reduce the difficulties of access to the Heitor Villa-Lobos symphonic repertoire through the study of piccolo solo excerpts in his works as well as proposing technical-interpretative assistance. The project also considers the quality of issues and dissemination of recordings of the studied pieces. Finally, it aims to compile a book of excerpts from analyzed works.